2021
DOI: 10.1111/apa.16034
|View full text |Cite
|
Sign up to set email alerts
|

Growth assessment of children during the COVID‐19 pandemic—Can we rely on parental measurements?

Abstract: Aim The COVID‐19 pandemic prompted the rapid development of remote medical services. During lockdown periods, children's growth data were obtained from parents’ home assessments. This study aimed to assess the accuracy of home height and weight measurements and analyse their utility in clinical decision‐making. Methods A retrospective, single‐centre observational study. Children aged 3–18 years were measured for weight and height at home using guidance provided to parents on proper measurements techniques befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
12
3
1
Order By: Relevance
“…Zhou et al (24) raised concerns about the accuracy of self-reported weight and height of Chinese adolescents, and He et al (25) found that parent-reported BMI tended to overestimate the prevalence of obesity in children and adolescents. A study of the accuracy of parental measurements of height and weight during COVID-19 found lower BMI at home than in clinics (26). Although the accuracy analysis of this study suggested that the parentreported data was reliable, we found that the BMI z-score of mobile-based data was higher than those of hospital-based data in this study, especially among school-aged children.…”
Section: Discussioncontrasting
confidence: 81%
“…Zhou et al (24) raised concerns about the accuracy of self-reported weight and height of Chinese adolescents, and He et al (25) found that parent-reported BMI tended to overestimate the prevalence of obesity in children and adolescents. A study of the accuracy of parental measurements of height and weight during COVID-19 found lower BMI at home than in clinics (26). Although the accuracy analysis of this study suggested that the parentreported data was reliable, we found that the BMI z-score of mobile-based data was higher than those of hospital-based data in this study, especially among school-aged children.…”
Section: Discussioncontrasting
confidence: 81%
“…School-scale weights were taken on a portable SECA digital scale, Model 813 (SECA, Hamburg, Germany; 440 pounds) which is accurate within 0.1 pounds over a range from 1 to 440 pounds [ 16 ]. Home scale weights were taken on an existing home scale (models not noted) or on a scale provided by the research team that was widely available during the time of the pandemic despite supply chain and shipping issues experienced at that time (Etekcity High Precision Digital Body Weight Bathroom Scale with Ultra-Wide Platform and Easy-to-Read Backlit LCD; 440 Pounds).…”
Section: Methodsmentioning
confidence: 99%
“…Another study observed that caregivers of children with overweight/obesity under-reported their child’s height measurements resulting in a difference of 0.86 cm compared to a difference of 0.1 cm for children in the normal weight category. Despite these differences in height measurements, caregivers reported comparable weight measurements [ 16 ] across all weight classifications. It remains unclear how accurate remote height or weight measurements are for school-aged children.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study conducted during the current COVID-19 pandemic in a single pediatric endocrinology center demonstrated that remote measurements among a cohort ranging from 3 to 18 years could be clinically useful due to their overall good concordance with in-person measurements ( 6 ). Interestingly, remote, parent-provided measurements of overweight and obese children were deflated for height.…”
Section: The Rise Of Remote Anthropometrymentioning
confidence: 99%
“…Even in clinical settings, it is not uncommon for a documented measurement to be corrected during the same visit after the care provider plots the value in the infant's growth chart, realizes that the growth curve has an unexpected shape, and decides to take a second measurement. Older children can be measured for height and weight relatively easier than infants, since household scales and measuring tapes will ordinarily be sufficient for accurate measurements, though there is the possibility of systematic or random errors arising from the equipment or measuring techniques ( 6 , 13 ). If these household tools are applied to infants for anthropometric measurements, the errors may further compound.…”
Section: Lack Of Validation In Infant Populationsmentioning
confidence: 99%